Online Habitus and Anti-Social Media in Gail Honeyman’s Eleanor Oliphant is Completely Fine - Lilja, Minna (My University, 2024)
Gail Honeyman’s contemporary novel Eleanor Oliphant is Completely Fine (2017) portrays social media as a fluid entity that can easily infiltrate one’s life. In this novel, Honeyman draws upon the features of the digital age and some of the impacts of social media on users. This paper examines the representation of social media and its consequences in Eleanor Oliphant is Completely Fine to gain a deeper understanding of (dis)connection in the digital age. The omnipresence of online spaces is inspected due to its relation to social media, and the novel’s characters’ perspectives, functions, and roles for social media in contemporary culture are studied. Moreover, I examine the opportunities and limitations of online spaces as represented in the novel. I employ Pierre Bourdieu’s theoretical thinking tools and concepts of habitus and social capital to explain and further analyse the underlying structures behind examined phenomena. I discuss how the rise of omnipresence, the culture of being chronically online and active, ironically enhances loneliness in users. I argue that social media, which was originally intended as a tool for connection, has instead become a means of exacerbating solitude.
Keywords: Gail Honeyman, Eleanor Oliphant is Completely Fine, social media, digital age, solitude